Enhancing Competitiveness through Strategic Analysis in the Makassar Coffee Shop Industry - Azmi, Mufidatul; Ikram M, Muhaidir; Huzaen, Chairunnisaa M. Z. (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the competitive strategy of Skena Coffee in navigating the intensifying market competition within Makassar’s rapidly expanding coffee shop industry. Utilizing a qualitative case study design, the research employs an integrated analytical approach comprising PESTEL, SWOT, IFAS, and EFAS frameworks to obtain a comprehensive assessment of the firm’s internal capabilities and external environmental conditions. The empirical findings demonstrate that Skena Coffee holds a strong internal strategic position, as indicated by an IFAS score of 3.06, supported by product differentiation, advantageous geographic placement, and consistent service quality. Concurrently, the company benefits from favorable external opportunities, reflected in an EFAS score of 3.12, including the increasing prevalence of coffee consumption and the rising influence of digital engagement on consumer behavior. The firm’s placement within Quadrant I of the IE Matrix denotes an aggressive “grow and build” strategic orientation, signaling a capacity to pursue expansion, innovation, and intensified market engagement. Based on this strategic mapping, the study proposes the adoption of Strength Opportunity (SO) strategies, particularly through market penetration via additional outlet development, continuous innovation and refinement of menu offerings aligned with shifting consumer preferences, and the enhancement of digital marketing systems through optimized social media utilization and strengthened online customer interaction. Collectively, these strategic directives are projected to reinforce Skena Coffee’s competitive positioning and support its long-term sustainability within the structurally dynamic and increasingly competitive F&B sector in Makassar.